Roman Architecture - Sear, Frank (Taylor & Francis Group, 2020)
Cover -- Endorsement Page -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- List of Figures -- Preface -- Acknowledgements -- Chapter 1 Republican Rome -- Notes -- Chapter 2 Roman Building Types -- Town planning -- Religious buildings -- Public buildings -- Basilicas -- Commercial buildings -- Domestic buildings -- Recreational buildings -- Entertainment -- Honorific monuments -- Utilitarian buildings -- Harbours and lighthouses -- Military and defensive architecture -- Funerary -- Notes -- Chapter 3 The Age of Augustus -- Notes -- Chapter 4 Roman Architects, Building Techniques and Materials -- Notes -- Chapter 5 The Julio-Claudians -- Notes -- Chapter 6 Two Roman Towns: Pompeii and Ostia -- Notes -- Chapter 7 The Flavians -- Notes -- Chapter 8 Trajan and Hadrian -- Notes -- Chapter 9 North Africa -- Notes -- Chapter 10 The European Provinces -- Spain -- France (Gaul) -- Britain -- The Rhine and Danube frontiers -- Germany (Germania superior and inferior) -- The Balkans -- Notes -- Chapter 11 The Eastern Provinces -- Greece -- Asia Minor -- Syria -- Arabia -- Notes -- Chapter 12 The Late Empire -- Notes -- Glossary -- Authors and passages cited -- Select Bibliography -- Index.